Teenage pregnancy: strategies for prevention. Issue 4 (April 2018) - Hadley, Alison
Abstract: Teenage pregnancy is a cause and consequence of inequality, limiting the life chances of young parents and their children. It is an issue of global concern, with many countries developing programmes of prevention. This review focuses on the experience of the England strategy, launched in 1999 to address the historically high rates. It is one of the few examples of a successful long term, multi-agency programme, led by national government and locally delivered which, between 1998 and 2015, reduced the under-18 conception rate by 55%. It sets out the case for helping young people delay early pregnancy, the international evidence for prevention, and how evidence is translated into a 'whole system' approach. Questions are included to encourage both investigation into local programmes on teenage pregnancy prevention, and reflection on individual practice. The review concludes with summarising the next steps for England and the lessons that can be shared more widely.